Green Supply Chain Management and Its Impact on Firm Competitiveness in Emerging Markets - Thanaporn Phattanaviroj; Rinruedee Pattaradej (PT Advanced business journal, 2025)
This study investigates the role of Green Supply Chain Management (GSCM) in enhancing firm competitiveness within emerging markets, where environmental sustainability and economic growth intersect amid infrastructural and regulatory challenges. A quantitative cross-sectional survey was conducted among 300 manufacturing firms across diverse sectors in emerging markets. Data were analyzed using regression and machine learning techniques to assess the relationship between GSCM practices and competitive advantage, moderated by organizational capabilities and market characteristics. The results reveal a positive, albeit complex, relationship between GSCM practices and firm competitiveness. While linear correlations appear weak, Random Forest analysis identifies GSCM practices and organizational capabilities as the most significant predictors of competitive advantage. Sectoral differences further highlight the contextual nature of GSCM effectiveness, with industries such as pharmaceuticals and food & beverage showing relatively higher performance outcomes. The findings underscore the strategic value of integrating sustainability into supply chain operations. Firms in emerging markets can leverage GSCM not only to comply with environmental regulations but also to enhance brand reputation, operational efficiency, and market responsiveness. This study contributes to the limited empirical literature on GSCM in emerging markets by offering a nuanced understanding of how green practices influence competitiveness. It highlights the importance of contextual factors and provides actionable insights for practitioners aiming to align sustainability with strategic business goals.